Monsoonal climate and asymmetric heating facilitate the slope-aspect to influence landscape-scale tree structure in the Western Ghats, India - Devi Maheshwori; Shreyas Managave; Girish Jathar; Sham Davande (Environmental Research Communications)
The regional variation of rainfall and length of the rainy season are identified to control the vegetation distribution in the Western Ghats (WG) of India, one of the important biodiversity hotspots. The asymmetric heating of various aspects in controlling vegetation distribution at landscape-scale, known at mid-latitudes, is not anticipated in the WG due to its lower latitudinal position. Here we demonstrate the existence and prevalence of two modes related to monsoonal climate and asymmetric solar heating that influence the vegetation structure at the landscape-scale in the WG: (i) the north-facing slopes have a higher tree cover (TC) and canopy height (CH) than the south-facing slopes and (ii) higher TC and CH on the west-facing slopes than the east-facing slopes. The asymmetry associated with these modes increases with the slope angle. Our study shows the slope-dependence of the north-south and west-east asymmetries in TC and CH is established by lower TC and CH selectively on the steeper south- and east-facing slopes. The net effect of these modes often leads northwest and southeast aspects to have the highest and lowest TC (and CH) at the landscape scale, respectively. We thus demonstrate that even in low-latitude regions, the slope-aspect plays an important role in determining the TC and CH heterogeneity at landscape-scale if the relief is higher. The role of aspect in controlling vegetation structure at landscape-scale needs to be considered while formulating and executing programs aimed at increasing tree cover and conserving biodiversity, especially in the high relief areas in the tropics having seasonal rainfall, such as in the WG.